Nursing team on the importance of religiosity and spirituality in death processes in an intensive care unit: literature review (Research, Society and Development, 2022)
This study aimed to seek scientific evidence that describes the perceptions of the nursing team regarding the importance of religiosity and spirituality in the processes of health recovery and/or acceptance of death in the Intensive Care Unit (ICU). This is an integrative literature review, carried out online through a scientific database Virtual Health Library (VHL) comprising the Scientific and Technical Literature of Latin America and the Caribbean (LILACS), Nursing Database (BDENF) ) and Medical Literature Analysis and Retrieval System Online (Medline); and Public Medline (PubMed), through the descriptors/MeSH: spirituality, religion, religious beliefs, nursing, intensive care unit, intensive care units, using the Booleans “AND” and “OR” and also books and materials on the topic in question. Two categories were developed “Spirituality as an integral part of holistic care” and “The importance of including spirituality, faith and religiosity in nursing curricula”. Themes related to religiosity and spirituality are poorly reflected by workers within the ICU. The symbolism and complexity of themes that involve the family and the nursing team, death, spiritual care, must be transposed to the formal curriculum of the nursing academy through courses, curricular activities and discussions.